Usage of Communicative Methods in Maharah Kalam Learning in SMP Muhammadiyah 8 Tanggulangin Sidoarjo - Farah Nabila Qurrata A’Yun; Imam Fauji (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to determine the application of communicative methods in teaching students' maharah kalam (speaking ability) and the supporting and inhibiting factors in its application at SMP Muhammadiyah 8 Tanggulangin Sidoarjo. This research uses qualitative methods to understand this phenomenon in depth from the perspective of students, teachers and other related parties. Data collection was carried out through observation, in-depth interviews and documentation. Meanwhile, data analysis uses data reduction, data presentation and data verification. Results The research results show that the application of communicative methods in teaching maharah kalam can be done in this way role playing (role playing), group discussions, use of interactive media and integration of language skills. Meanwhile, the supporting factors are institutional support, teacher competence and creativity, and student motivation and active participation. The inhibiting factors are limited learning facilities, variations in language abilities among students, limited mastery of methods by teachers, and technological barriers.